Sources of Sodium in US Adults From 3 Geographic Regions. Issue 19 (9th May 2017) - Harnack, Lisa J.; Cogswell, Mary E.; Shikany, James M.; Gardner, Christopher D.; Gillespie, Cathleen; Loria, Catherine M.; Zhou, Xia; Yuan, Keming; Steffen, Lyn M.
Abstract : Background: Most US adults consume excess sodium. Knowledge about the dietary sources of sodium intake is critical to the development of effective reduction strategies. Methods: A total of 450 adults were recruited from 3 geographic locations: Birmingham, AL (n=150); Palo Alto, CA (n=150); and the Minneapolis–St. Paul, MN (n=150), metropolitan areas. Equal numbers of women and men from each of 4 race/ethnic groups (blacks, Asians, Hispanics, and non-Hispanic whites) were targeted for recruitment. Four record-assisted 24-hour dietary recalls were collected from each participant with special procedures, which included the collection of duplicate samples of salt added to food at the table and in home food preparation. Results: Sodium added to food outside the home was the leading source of sodium, accounting for more than two thirds (70.9%) of total sodium intake in the sample. Although the proportion of sodium from this source was smaller in some subgroups, it was the leading contributor for all subgroups. Contribution ranged from 66.3% for those with a high school level of education or less to 75.0% for those 18 to 29 years of age. Sodium inherent to food was the next highest contributor (14.2%), followed by salt added in home food preparation (5.6%) and salt added to food at the table (4.9%). Home tap water consumed as a beverage and dietary supplement and nonprescription antacids contributed minimally to sodium intake (<0.5% each). Conclusions: Sodium added to food outside the home accounted for ≈70% of dietary sodium intake. This finding is consistent with the 2010 Institute of Medicine recommendation for reduction of sodium in commercially processed foods as the primary strategy to reduce sodium intake in the United States. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02474693. Abstract : Supplemental Digital Content is available in the text.